MAPPING RESEARCH DEVELOPMENTS AND TRENDS: SUSTAINABLE ECONOMIC LITERACY IN ISLAMIC CONTEXT - Mukti, Titania (At-Thullab : Jurnal Mahasiswa Studi Islam, 2025)
This study presents a bibliometric analysis of islamic sustainable economic research from scopus indexed scientific publications. Data sources were obtained from searches using the publish or perish application with the keywords “islamic AND sustainable AND economy” total of 205 articles from 2007-2024. Statistical analysis of metadata using the VOS Viewer application. This study analyzes the trend of research development based on the year of publication, journal contribution, journal citation, country, co-authorship, authors, keywords used, and visualization analysis of the research landscape cluster. The results show that the keywords "sustainable development", "islamic finance", and "waqf" can be said to be developing quite well because each year shows an increase in the number of studies relevant to these keywords. The author who produces the most article is M. Kabir Hassan with 7 articles. The most articles were produced in 2022 with total 28 articles. Malaysia is the most contributing country to publish 64 articles. Research clusters consisting of 10 clusters. The direction of future research development that still rarely researched in the role of Islamic microfinance for sustainable economic development, Islamic financial performance to realize a sustainable economy, politics and regulation for an Islamic-based sustainable economy